Undisclosed human immunodeficiency virus risk factors identified through a computer‐based questionnaire program among blood donors in Brazil. Issue 11 (22nd March 2013) - Blatyta, Paula Fraiman; Custer, Brian; Gonçalez, Thelma Terezinha; Birch, Rebecca; Lopes, Maria Esther; Lopes Ferreira, Maria Ines; Carneiro Proietti, Anna Barbara; Sabino, Ester Cerdeira; Page, Kimberly; de, Cesar; ,
<x xml:space="preserve">Abstract</x> Background Human immunodeficiency virus (HIV) risk factor screening among blood donors remains a cornerstone for the safety of blood supply and is dependent on prospective donor self‐disclosure and an attentive predonation interview. Audio computer‐assisted structured interview (ACASI) has been shown to increase self‐reporting of risk behaviors. Study Design and Methods This cross‐sectional study was conducted between January 2009 and March 2011 at four Brazilian blood centers to identify the population of HIV‐negative eligible blood donors that answered face‐to‐face interviews without disclosing risks, but subsequently disclosed deferrable risk factors by ACASI. Compared to the donor interview, the ACASI contained expanded content on demographics, sexual behavior, and other HIV risk factors questions. Results A total of 901 HIV‐negative blood donors were interviewed. On the ACASI, 13% of donors (n = 120) declared a risk factor that would have resulted in deferral that was not disclosed during the face‐to‐face assessment. The main risk factors identified were recent unprotected sex with an unknown or irregular partner (49 donors), sex with a person with exposure to blood or fluids (26 donors), multiple sexual partners (19 donors), and male–male sexual behavior (10 donors). Independent factors associated with the disclosure of any risk factor for HIV were age (≥40 years vs. 18‐25 years; adjusted odds ratio [AOR], 0.45; 95% confidence interval [CI], 0.23‐0.88) and blood center (Hemope vs. Hemominas; AOR, 2.51; 95% CI, 1.42‐4.44). Conclusion ACASI elicited increased disclosure of HIV risk factors among blood donors. ACASI may be a valuable modality of interview to be introduced in Brazilian blood banks.